In Gutenbergs Fußstapfen: Translatio typographica Zum Verhältnis von Typografie und Translation - Schopp, Jürgen (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractEver since Johannes Gutenberg’s times, typography has shaped the visual appearance of the written word in western cultures. Gutenberg’s invention gave birth to a development that has changed the appearance of the written message considerably compared to scriptographically manufactured texts. Texts that have been carefully typographically designed still serve as examples both to emulate and also to aim for in desktop publishing. Therefore, the typographical tradition is of essence even in the era of the computer and has resulted in a dichotomy of typographic design (non-professional vs. professional typographic). Hence, all texts that are intended to be translated form part of a bi- or even multi-coded textual network and exist, in one way or another, as typographically designed texts. Equally, a translation project starts as an unfinished product and must undergo, as a rule, some typographical process prior to printing and publication. Therefore, typography is a factor that needs to be taken into consideration under the double aspect of professional translation and the education of translators.1. Typography is a semiotic phenomenon, which means that all typographical symbols are specific to their individual cultures and, hence, have different meaning. Also, various cultures will use these symbols with varied frequency. What is more, authors of literary texts may employ typographical symbols intentionally as a special characteristic of the text or as part of it.2. Typography needs to be considered in the light of the visual appearance of a text, a fact that serves to demonstrate the significance of, firstly, knowledge of a particular culture of typographical symbols; secondly, of typographical conventions of source and target culture (orthotypography); and thirdly, of a solid understanding into the professional production process of typographically produced publications.